Evaluation of Ge-doped silica fibre TLDs forin vivodosimetry during intraoperative radiotherapy - Moradi, Farhad; Ung, Ngie Min; Mahdiraji, Ghafour Amouzad; Khandaker, Mayeen Uddin; See, Mee Hoong; Taib, Nur Aishah Mohd; Bradley, David Andrew (IOP Publishing, 2019)
Ge-doped silica fibre (GDSF) thermoluminescence dosimeters (TLD) are non-hygroscopic spatially high-resolution radiation sensors with demonstrated potential for radiotherapy dosimetry applications. The INTRABEAM® system with spherical applicators, one of a number of recent electronic brachytherapy sources designed for intraoperative radiotherapy (IORT), presents a representative challenging dosimetry situation, with a low keV photon beam and a desired rapid dose-rate fall-off close-up to the applicator surface. In this study, using the INTRABEAM® system, investigations were made into the potential application of GDSF TLDs for in vivo IORT dosimetry. The GDSFs were calibrated over the respective dose- and depth-range 1 to 20 Gy and 3 to 45 mm from the x-ray probe. The effect of different sizes of spherical applicator on TL response of the fibres was also investigated. The results show the GDSF TLDs to be applicable for IORT dose assessment, with the important incorporated correction for beam quality effects using different spherical applicator sizes. The total uncertainty in use of this type of GDSF for dosimetry has been found to range between 9.5% to 12.4%. Subsequent in vivo measurement of skin dose for three breast patients undergoing IORT were performed, the measured doses being below the tolerance level for acute radiation toxicity. © 2019 Institute of Physics and Engineering in Medicine.